Odliczenie darowizn na rzecz kościoła od dochodu w podatku dochodowym od osób fizycznych – ewolucja regulacji prawno-podatkowych oraz kierunki wykładni - Selera, Paweł (Kwartalnik Prawa Podatkowego, 2016)
Significantly, however, is that the legal basis for this type of deduction is on the one hand, the “classic” tax law – which is obvious – but also in the various laws regulating the relation of the state to the individual churches. However the scope of said deduction was different in tax law with provided limitation for donations up to 10% of income earned and in “church law” with deduction for donation without any limits. The dispute as to priority of tax law in relation to “church law” had to settle in the resolution the Polish Supreme Administrative Court. This example shows how carefully any changes to the tax law should be made, not to question the tax preferences guaranteed by other legal acts. However in my view bearing in mind the principle legal certainty any tax preferences (deductions / allowances / exemptions) should be directly and exclusively established in tax law and not in other legal acts.